Optimization and in vitro toxicity evaluation of G4 PAMAM dendrimer–risperidone complexes - Prieto, Maria Jimena (2011)
Risperidone is an approved antipsychotic drug belonging to the chemical class of benzisoxazole. This drug has low solubility in aqueous medium and poor bioavailability due to extensive first-pass metabolism and high protein binding (>90%). As new strategies to improve treatments efficiency are needed, we have studied cationic G4 PAMAM dendrimers’ performance to act as efficient nanocarriers for this therapeutic drug. In this respect, we explored dendrimererisperidone complexation dependence on solvent, temperature, pH and salt concentration, as well as in vitro cytotoxicity measured on L929 cell line and human red blood cells. The best dendrimererisperidone incorporation was achieved when a mixture of 70:30 and 90:10 v/v chloroform:methanol was used, obtaining 17 and 32 risperidone molecules per dendrimer, respectively. No cytotoxicity on L929 cells was found when dendrimer concentration was below 3 x 10 -2 µM and risperidone concentration below 5.1 µM. Also, no significant hemolysis or morphological changes were observed on human red blood cells. Finally, attempting to obtain an efficient drug delivery system for risperidone, incorporation in G4 PAMAM dendrimers was optimized, improving drug solubility with low cytotoxicity.